Role of Calcimimetics in Treating Bone and Mineral Disorders Related to Chronic Kidney Disease - Yi-Chou Hou; Cai-Mei Zheng; Hui-Wen Chiu; Wen-Chih Liu; Kuo-Cheng Lu; Chien-Lin Lu (Pharmaceuticals, 2022)
Renal osteodystrophy is common in patients with chronic kidney disease and end-stage renal disease and leads to the risks of fracture and extraosseous vascular calcification. Secondary hyperparathyroidism (SHPT) is characterized by a compensatory increase in parathyroid hormone (PTH) secretion in response to decreased renal phosphate excretion, resulting in potentiating bone resorption and decreased bone quantity and quality. Calcium-sensing receptors (CaSRs) are group C G-proteins and negatively regulate the parathyroid glands through (1) increasing CaSR insertion within the plasma membrane, (2) increasing 1,25-dihydroxy vitamin D3 within the kidney and parathyroid glands, (3) inhibiting fibroblast growth factor 23 (FGF23) in osteocytes, and (4) attenuating intestinal calcium absorption through Transient Receptor Potential Vanilloid subfamily member 6 (TRPV6). Calcimimetics (CaMs) decrease PTH concentrations without elevating the serum calcium levels or extraosseous calcification through direct interaction with cell membrane CaSRs. CaMs reduce osteoclast activity by reducing stress-induced oxidative autophagy and improving Wnt-10b release, which promotes the growth of osteoblasts and subsequent mineralization. CaMs also directly promote osteoblast proliferation and survival. Consequently, bone quality may improve due to decreased bone resorption and improved bone formation. CaMs modulate cardiovascular fibrosis, calcification, and renal fibrosis through different mechanisms. Therefore, CaMs assist in treating SHPT. This narrative review focuses on the role of CaMs in renal osteodystrophy, including their mechanisms and clinical efficacy.